2013
DOI: 10.15835/nsb529017
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Seed Priming and Accelerated Aging on Germination and Physiochemical Changes in Milk Thistle (Silybum marianum)

Abstract: Effects of seed priming and aging on some physiological characteristics of Milk thistle was studied in a factoral experiment based on Complete Randomized Design (CRD). Tratments were included hydro priming (using distilled water), halo priming (0, 1.5, 3, 4.5 and 6% KNO 3 ) and accelerated aging (0, 2, 4 and 6 days under 45°C and 95% humidity) in three replications. Determined parameters were germination charactristics including germination percentage, daily germination speed, mean time of germination, seed vi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 36 publications
1
6
0
2
Order By: Relevance
“…Potassium is important for certain enzymes (Taiz and Zeiger, 2006), as it increases their activity and neutralizes the negative effects of free radicals (Hu and Schmidhalte, 2005). This pre-sowing treatment led to an increase in germination by means of reduction in lipid peroxidation and improvement of antioxidant activity (Parmoon, 2013).…”
Section: Resultsmentioning
confidence: 96%
“…Potassium is important for certain enzymes (Taiz and Zeiger, 2006), as it increases their activity and neutralizes the negative effects of free radicals (Hu and Schmidhalte, 2005). This pre-sowing treatment led to an increase in germination by means of reduction in lipid peroxidation and improvement of antioxidant activity (Parmoon, 2013).…”
Section: Resultsmentioning
confidence: 96%
“…Similarly, Jowkar et al (2012) concluded that faster germination in primed seeds of milk thistle was due to enhanced activities of antioxidant enzymes and higher soluble protein levels in the seed. Other researchers have also declared the beneficial effects of priming for improvement of emergence potential and stand establishment of milk thistle seeds under abiotic stresses (Parmoon et al, 2013;Nasiri et al, 2014). Improved early seedling growth, nutrient partitioning and higher chlorophyll contents are important manifestations of seed priming with Ca and K salts (Afzal et al, 2012b).…”
Section: Discussionmentioning
confidence: 99%
“…For Leymarie et al (2012) it is possible that this decrease in H 2 O 2 was partly related to the slight increase of CAT activity, because these events in the embryonic tissues are associated with the completion of germination in seeds. In the other hand, Parmoon et al (2013) observed that Catalase and Peroxidase activity was reduced during aging because of the increase in H 2 O 2 and free radicals in the stressed cell cytoplasm during oxidative stress, leading to a reduction of seed viability.…”
Section: Resultsmentioning
confidence: 99%